Transesterification of cooking palm oil via Mn-Al mixed oxides catalysts: effects of metal ratio / Siti Athirah Ramli … [et al.] - Ramli, Siti Athirah; Wan Kamis, Wan Zuraida; Ali Bashah, Nur Alwani; Inderan, Vicinisvarri; Isa, Norain (Universiti Teknologi MARA Cawangan Pulau Pinang, 2025)
The abstract Biodiesel or fatty acid methyl ester (FAME) is an environmentally friendly fuel that is an alternative to diesel fuel. In this study, mixed oxides catalysts of Mn-Al were synthesised via the sol-gel method at various metal ratios and used in the transesterification of cooking palm oil (CPO) to produce FAME. The reactions were conducted in a batch reactor at a temperature of 55 °C, with a reaction time of 3 h and a catalyst loading of 2.5 wt%. The effects of Mn:Al metal weight ratios of 1:1, 1:2, 2:1, 0:1, and 1:0 were investigated based on the FAME density obtained from the reaction. The thermal stability and the presence of surface functional groups were investigated using thermal gravimetric analysis (TGA) and Fourier-transform infrared spectroscopy (FTIR), respectively. The results show that the Mn-Al catalyst prepared at 1:2 metal weight ratio and calcined at 500 °C for 2 h obtained a FAME density of 862 kg/m3, which is the closest to standard palm oil biodiesel density. The catalysts with different metal ratios contained similar active surface functional groups. The TGA analysis of the Mn-Al metal ratio 1:2 showed no significant weight loss observed after 300 °C, indicating good thermal stability. The findings indicate that Mn-Al mixed oxides have the potential as heterogeneous catalyst in the transesterification of CPO to produce FAME.